2021
DOI: 10.11648/j.jfa.20210902.14
|View full text |Cite
|
Sign up to set email alerts
|

The Design of Stratified Contingent Bank Liability Structure to Release Risk Incentive Effects

Abstract: This paper proposes a new type of bank liability structure with stratified contingent capital based on the suggestions of Basel III and TLAC Term Sheet. It try to solve the problem that the total loss absorbing capacity of global systemically important banks is insufficient and the single contingent capital-CoCos will bring extra risk to the bank in recent years. Compared with single contingent capital, the bail-in mechanism of stratified contingent capital is more complex and its risk effects will be more unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…It is observed that finte ch indirectly augments banks' liability expenses, leading to a heightened dependence on interbank liabilities as a countermeasure . Lin and Xuezhi (2021) came up with a new liability structure based on Basel III and the Total Loss-Absorbing Capacity (TLAC) Term Sheet. This structure focused on layered contingent capital and the possible effects of fintech on banking vulnerabilities.…”
Section: Fintech Liability Structure and Bank Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…It is observed that finte ch indirectly augments banks' liability expenses, leading to a heightened dependence on interbank liabilities as a countermeasure . Lin and Xuezhi (2021) came up with a new liability structure based on Basel III and the Total Loss-Absorbing Capacity (TLAC) Term Sheet. This structure focused on layered contingent capital and the possible effects of fintech on banking vulnerabilities.…”
Section: Fintech Liability Structure and Bank Riskmentioning
confidence: 99%
“…Secondly, the use of the mediating role of the liability structure. Wang and Qin (2021) proposed a ne w type of bank liability structure. However, our Equation 2 directly addresses the mediating role of liabilit y structure in the relationship between fintech and commercial bank risk, which was not the core focus of their research.…”
Section: Model Designmentioning
confidence: 99%